PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DALAM PENUNJANG KEPUTUSAN KEPESERTAAN PASIEN ICU PADA BPJS - Aidil Rizki Hidayat; Yuma Akbar; Dadang Iskandar Mulyana (Cross-border, 2021)
The Health Social Security Administering Body (BPJS Kesehatan) currently uses a manual system in determining the class of care, where participants choose which treatment class to choose for themselves. While the treatment class that must be selected is not in accordance with the policies determined by the BPJS Health. Sometimes the participants choose treatment classes that are not in accordance with the abilities of the participants. They prefer a lower class because the monthly pay is low so they should be able to choose a higher class of care based on the criteria of the job. Under these provisions, this decision support system will assist BPJS Health in determining the treatment class for the participants by looking at the criteria of the participants' work so that the participants cannot choose their own treatment class. The system is designed using the Simple Additive Weighting (SAW) method because it is able to select the best alternative from a number of alternatives. for time efficiency in determining the class of participants. Based on the results of system testing, the following conclusions can be drawn: In this decision support system, 3 treatment classes are obtained which can be determined by criteria for each treatment class based on sub-criteria in the form of Non PBI and PBI, this Simple Additive Weighting method has weaknesses in changing the existing criteria so that should add to the normalization assessment. The advantage is that this method can make it easier to determine the solution.